Bladder stone formation over a partially migrated intrauterine contraceptive device in a patient presenting with cyclical haematuria - R Rajan (South African Medical Association, 2014)
The case of a 42-year-old woman with a forgotten intrauterine contraceptive device (IUCD) presenting with irritative bladder symptoms and cyclical haematuria is reported. The threads of the IUCD were seen in the vagina during speculum examination. Partial migration of the IUCD into the bladder and formation of a large stone around it were confirmed by X-ray of the kidney, ureter and bladder and cystoscopy. Suprapubic cystolithotomy was performed, and the stone was removed together with the IUCD.